The Roles of Leadership Principal to Improving of Education Quality through Managerial Competence - Wibowo, Wisnu Dwi; Wakhudin, Wakhudin (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2021)
This study aims to describe the leadership process of principals with managerial competencies to improve the quality of education in primary schools. Initial observations show that there are still many school principals in the Adipala sub-district, Cilacap, who have not carried out their primary duties and functions correctly as leaders of educational units. The principal is the person who is responsible for and leads the school in managing school resources to achieve academic goals. The method used in this research is a qualitative approach to phenomenological studies. The informants in this study were five public elementary school principals in the Adipala sub-district. Data collection techniques by interview, observation, and study documentation. Activities in data analysis are data reduction, data presentation, and concluding. The results showed that principal leadership with excellent and practical managerial competence could improve the quality of education in primary schools.